MAKNA HADIS ANJURAN PEREMPUAN SHALAT BERJEMAAH KE MESJID DAN SHALAT DI RUMAH - Muhammad Amin (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2015)
This study of women with regard to the primacy of prayer in the home and in the mosque. The results showed some of the main criteria more women praying in mosques, namely: women who have aged, women around, The girl who did not attract the attention of young people. Some criteria better women pray at home, namely: a beautiful woman, A mother who had small children, and women who have been older